2019
DOI: 10.2139/ssrn.3509657
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Article Processing Charges in Open Access

Abstract: Large publishing companies have been dominating scientific publishing for long, which leads to high subscription fees and inhibited access to scientific knowledge. At digital era, the opportunity of an unrestricted access appears feasible, because the cost of publishing should be low. It is no longer the readers and libraries to pay subscription fees, but scientific organizations and authors themselves who pay for the cost of having their article published. As the data shows, there is a tremendous variance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Consequently, their OA pricing strategies can be altered toward making this option unattractive to authors, delaying this change to prolong a perception of inevitability. These data were corroborated by Budzinski et al (Budzinski et al 2020), who found that large publishers and hybrid journals have greater APCs.…”
Section: Introductionsupporting
confidence: 62%
See 4 more Smart Citations
“…Consequently, their OA pricing strategies can be altered toward making this option unattractive to authors, delaying this change to prolong a perception of inevitability. These data were corroborated by Budzinski et al (Budzinski et al 2020), who found that large publishers and hybrid journals have greater APCs.…”
Section: Introductionsupporting
confidence: 62%
“…This drift was confirmed by our data from non-profit national publishers to international high impact commercial publishers. In addition to reputation, the quality and speed of the review process or publication time of the mega journals can also be considered (Budzinski et al 2020) as one of the reasons for the increase in Brazilian articles at these larger periodicals. This work sought to analyze APC spending in Brazil in the 2012-2019 period and its possible implications for Brazilian research.…”
Section: Minnitti Et Al (mentioning
confidence: 99%
See 3 more Smart Citations